Recovery Kawasan Bencana: Perwujudan Trauma Healing Melalui Kegiatan Psikologi dan Rohani - Koentjoro -; Budi Andayani (Universitas Islam Indonesia, 2007)
After Indonesia has undergone the natural disasters, it is urgent need to increase the role of psychology in coping the disaster victims. The increasing of this role is not only relating to method of help. Hence, it is needed to be stabilized a form pattern what should do to the victims. The role of psychology that focusing on the process of mental and behavior can be not centralize on the coping of stress and increasing solving be havior. Briefly, the role of psychology in this sense beside the passive coping, it needs to be an active coping.